Porcine alanine transaminase after liver allo-and xenotransplantation - Ekser, Burcin (2012)
Aspartate transaminase (AST) and alanine transaminase (ALT) are measured following liver transplantation as indicators of hepatocellular injury. During a series of orthotopic liver allo-and xenotransplants, we observed that there was an increase in AST in all cases. The anticipated concomitant rise in ALT did not occur when a wild-type (WT) pig was the source of the liver graft, but did occur when a baboon or a genetically engineered (α1,3-galactosyltransferase gene-knockout [GTKO]) pig was the source of the graft. We hypothesized that the cience of Galα1,3 Gal in GTKO pig livers may render pig hepatocytes similar to human and baboon hepatocytes in their response to hepatocellular injury. Reviewing the literature, after WT pig liver allotransplantation or xenotransplantation, in the majority of reports, although changes in AST were reported, no mention was made of changes in ALT, suggesting that there was no change in ALT. However, Ramirez et al. reported two cases of liver xenotransplants from hCD55 pigs, following which there were increases in both AST and ALT, suggesting that it is not simply the cience of expression of Galα1,3 Gal that is the cause. We acknowledge that our observation is based on a small number of experiments, but we believe it is worth recording.